Status and Condition of the Ancient Script to Support Document Activity in Kabupaten Ciamis - Sukaesih; Siti Khadijah, Ute Lies; Yanto, Andri; Budiono, Agung; Mulyani, Sri (International Journal of Psychosocial Rehabilitation, 2019)
There are 15 scripts has succeded been found in Ciamis Regency, but only three scripts the inventory and description clearly its form and its content. It proves that there are many ancient scripts has not been identified their existance by the department or researchers, as the result, there is no description about the form or the content of the script seeing the different owner of the script and how very little the the effort to protect the ancient script physically it may potentially be extinct quickly from the community. One of the activity that support the preservation of cultural inheritance is by document it. The purpose of the research is to know the status and the condition of the ancient script to support the activity of document. The research method which is used is qualitative with the design of research action. The result of this reseach shows that (1) identify the existance of the ancient script. (2) indentify the ancient script from social cultural side. (3) how the local people treat the ancient script. The conclusion of this research is status and condition of the ancient script in Ciamis Regency less concern because the community understanding about how important the ancient script is for the cultural inheritance continuity is still low